Pengaruh Pesan Iklan di Instagram terhadap Sikap Followers pada Produk - Renita Kurnia (Jurnal Inovasi Komunikasi, 2024)
The diversity of sandals is inseparable from fashion trends in the past. Blues Sandals, as one of Bandung's local fashion brands, uses Instagram to market its products through advertising activities. The purpose of this study is to determine the effect of advertising messages on Instagram on followers' attitudes towards products. The theory used is cognitive response theory. This study uses an explanatory method with simple random sampling technique. Questionnaires will be distributed to 98 respondents. The results of the questionnaire analysis using simple linear regression show that there is an influence of advertising messages on Instagram on followers' attitudes towards the product.